Concentrations of pro- and anti-apoptotic proteins, as well as calcium ions in mitochondria of endometrioid adenocarcinoma cells depending on the degree of its differentiation - E. M. Frantsiyants; I. V. Kaplieva; I. V. Neskubina; Yu. А. Petrova; A. P. Menshenina; L. K. Trepitaki; N. S. Lesovaya; V. A. Bandovkina; E. I. Surikova; M. L. Adamyan; O. E. Zhenilo; M. A. Rogozin; et al. (Исследования и практика в медицине)
Purpose of the study. To study the concentration of calcium ions, pro- and antiapoptotic proteins (cytochrome C, AIF-1, and Bcl-2) in the mitochondria of endometrioid adenocarcinoma (EA) cells in oncogynecological patients, depending on the degree of differentiation of malignant cells.Patients and methods. The study included patients who had undergone surgical treatment for endometrial adenocarcinoma (n = 42) and uterine fibroids (n = 14). The patients with endometrial adenocarcinoma were further classified as having highly differentiated (G1) disease, moderately differentiated (G2) disease, or poorly differentiated (G3) disease. The average age of patients with endometrial adenocarcinoma was 60.8 ± 2.9 years, and the average age of patients with fibroids was 49.4 ± 2.5 years. It is noteworthy that the patients in this study did not receive any neoadjuvant treatment. The concentration of cytochrome C (ng/mg protein), AIF (pg/mg protein), Bcl-2 (pg/mg protein), and calcium (mM/mg protein) was determined in the mitochondria of EA, fibroids, and intact uterus cells by ELISA. The statistical analysis of the results was performed using the Statistica 10.0 software package.Results. A decline in the degree of tumor cell differentiation was accompanied by a decrease in calcium levels within the mitochondria, with G2 and G3 exhibiting an average reduction of 2.0 times compared to the intact uterus. Furthermore, the Bcl-2 content in the tumor mitochondria at G3 demonstrated an average increase of 1.9 times compared to G1 and G2 (p < 0.05). Furthermore, the cytochrome C level at G1 was found to be 2.2 times higher than at G2 and 1.9 times higher (p < 0.05) than at G3. In the mitochondria of cells with G3 differentiation, the highest AIF-1 values were observed, which were 2.1 times higher than in intact cells and 1.9 times higher (p < 0.05) compared to the values in the mitochondria of myoma cells.Conclusions. It is hypothesized that the process of apoptosis is suppressed in the mitochondria of endometrioid adenocarcinoma cells due to an accumulation of Bcl-2 and a decrease in calcium. This accumulation of Bcl-2 and decrease in calcium activates energy processes, leading to the accumulation of cytochrome C and AIF-1. The severity of the biochemical events identified in the mitochondria of endometrioid adenocarcinoma increases with the degree of malignancy of the tumor cells. This increase in severity appears to contribute to an escalation in the aggressiveness of the tumor.